2010
DOI: 10.1111/j.1365-2648.2010.05459.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with advanced Parkinson’s disease: a constant struggle with unpredictability

Abstract: Parkinson's disease leads to profound bodily restrictions. Living with an unpredictable body affects all aspects of life, and nurses need to be aware of the impact the disease has on the entire lifeworld, and how this may affect the way treatment is perceived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(178 citation statements)
references
References 45 publications
2
169
1
6
Order By: Relevance
“…Qualitative research also explores the context of participants’ subjective experience. A hermeneutic phenomenological approach, informed by the philosophical constructs of Heidegger [27] Gadamer [28, 29] and Van Manen [30–32] was undertaken to study the complexities of a challenging life world [33]. Hermeneutic phenomenology is concerned with the study of lifeworld or human experience as we live it [30–33].…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research also explores the context of participants’ subjective experience. A hermeneutic phenomenological approach, informed by the philosophical constructs of Heidegger [27] Gadamer [28, 29] and Van Manen [30–32] was undertaken to study the complexities of a challenging life world [33]. Hermeneutic phenomenology is concerned with the study of lifeworld or human experience as we live it [30–33].…”
Section: Methodsmentioning
confidence: 99%
“…As well as monitoring the impact of changes to symptoms on community participation, it can also capture the broader impact of the treatment itself. Qualitative investigation of the impact of PD and its treatments has indicated, for example, that medications requiring a strictly timed regime can result in surrendering of valued activities and roles because leaving the house needs to be arranged around medication requirements [25]. Also, intensive rehabilitation programs requiring frequent hospital-based attendance may affect patterns of Lifespace.…”
Section: Introductionmentioning
confidence: 99%
“…Other qualitative studies showed (1) the severity of the disease and the functional status of the patient [19], (2) depression, disability, motor impairment, postural instability and cognitive impairment [20] and (3) nocturnal sleep disturbance, together with depressive symptoms and severity of motor symptoms, highly influence the QoL of patients [21]. Other qualitative studies have shown that the unpredictability of PD [22], the role of partners [23] and mental and psychosocial symptoms [24] highly influence the QoL of people with PD.…”
Section: Introductionmentioning
confidence: 99%